Investigations on morphology and photophysical characteristics of CH3NH3PbI3 polycrystalline films - Kadro, Jeannette (2014)
Mesoscopic superstructured solid state solar cells based on organic-inorganic lead halide perovskites have recently emerged as alternative to dye sensitized solid state solar cells. This work focuses on thorough morphological characterization of solution-processed CH3NH3PbI3 and on the identification of factors affecting the morphology of the crystallized product. It is shown that the material can adopt a wide range of morphological habits. The results allow insight into possible electron pathways important for both device optimization and understanding of working principle. Fluorescence Lifetime Imaging allows to spatially resolve emerging fluorescence and correlate differences in lifetimes to morphological features. Cathodoluminescence mapping allows investigating phase distribution in CH3NH3PbI3 polycrystalline coatings prepared by different methods and indicates formation of multiple phases exhibiting CL in the visible range. A study on stability of material and devices in local ambient conditions shows rapid degradation of material and device performance under exposure to high relative humidity.